Teachers’ Receptiveness to Opposing Views: A Cross-Cultural Scale Adaption and Evaluation - Esther Kaufmann (SAGE Open, 2025)
Teachers continuously make numerous judgments and engage with various educational stakeholders, whose perspectives are eventually integrated into their judgments. Given the differing viewpoints of these stakeholders, one may ask how receptive teachers are to diverse perspectives. In the present study, a German adaption of the Minson's Receptiveness to Opposing Views scale for German-speaking teachers and non-teachers was introduced as the first German instrument for cross-cultural comparisons. To evaluate the scale, a cross-cultural comparison was conducted (358 US and German teachers). After the validity and reliability of the German version of the Receptiveness to Opposing Views scale were confirmed, English- and German-speaking teachers significant differences between their overall scale results and their results for the subscales of Intellectual Curiosity, Derogation of Opponents, and Taboo Issues were found. A research agenda and its implications for practice, teacher development, and education is presented.